Analysis Of Library Visitors' Interest Using Factor Analysis And Discriminant Analysis - Hery Santono; Eko Sediyono; Hindriyanto Dwi Purnomo (INOVTEK Polbeng - Seri Informatika, 2025)
The relevance of libraries as learning centers, gathering places for the scientific community, and access points for resources not always available online underscores the importance of understanding the factors that influence library visitor interest. This study aims to analyze the factors impacting visitor interest using Factor Analysis and Discriminant Analysis. The key factors explored include service quality, comfort of facilities, quality of book collections, access to digital technology, and frequency of visits. Data was collected through surveys conducted with 500 library visitors across five different locations over a three-month period. Factor Analysis revealed that comfort factors and access to technology were the most significant variables influencing visitor interest, accounting for 65% of the variance in visitor behavior. Discriminant Analysis further classified visitors into high and low interest groups, showing that library facilities were the primary differentiator between these two groups. The study found that visitors with high interest were more likely to be influenced by the library's physical comfort and technology access, while those with low interest were less engaged with the library's services. This research provides valuable insights for library managers to enhance services, optimize library environments, and incorporate technological advancements to increase visitor engagement. It also contributes to the theoretical understanding of library management by identifying key factors that affect visitor interest, which can inform future strategies in the field. However, this study is limited by its cross-sectional nature, and the results may not be generalizable to other regions or visitor demographics. Future research could explore longitudinal data to assess how visitor preferences evolve over time.